Stormchaser / 2. - Stewart, Paul, 1955- (Stewart, Paul, 1955- Edge chronicles., 2004)
In his continuing adventures, Twig, now sixteen years old, joins the crew of his father's sky pirate ship and embarks on a dangerous mission to collect the powerful stromphrax, a substance that purifies water and also prevents the city of Sanctaphrax from floating away.